Simulation of COVID-19 trend in Selangor via SIR Model of infectious disease / Suzanawati Abu Hassan ... [et al.] - Abu Hasan, Suzanawati; Yeong, Kin Teoh; Mohd Nasir, Diana Sirmayunie; Sharil, Nur Shamira (Universiti Teknologi MARA, Perlis, 2022)
Coronavirus Disease 2019 (COVID-19) was initially reported in December 2019 in Wuhan City, China, as a result of a respiratory pandemic. Since then, the infection has spread rapidly and uncontrollably around the globe, prompting the World Health Organization (WHO) to declare it a pandemic. The study's overall objective is to imitate the COVID-19 infectious trend in Selangor. The SIR model is used to forecast infection and the course of COVID-19 diffusion and estimate the fraction of the population infected. As a result, the Susceptible, Infectious, and Recovered (SIR) model was used to accomplish the study's aims. From March 23, 2020, to June 30, 2020, 100 days of COVID-19 data were extracted from a database on the Malaysian Ministry of Health's website. The RStudio software was used to analyse data on infectious trends in this study. The SIR model is used to predict the basic reproduction ratio, , based on actual and simulated infectious trends for comparison. The value of the basic reproduction ratio for simulating the infectious trend is 2.0, and the basic reproduction ratio for modelling the infectious trend with the entire population of Selangor is 1.15429. According to the findings of this study, the reproduction ratio would affect the number of infected individuals by reducing the number of recovered individuals. The effectiveness of lockdown in preventing COVID-19 disease in Selangor was demonstrated by a significant reduction in the basic reproduction ratio.